Aluminium oxide nanowires synthesis from high purity aluminium films via two-step anodization. (May 2015) - Nazemi, Azadeh; Najafian, Ahmad; Seyed Sadjadi, Seyed Abolfazl
Highlights: Close-packed structure of Anodic Aluminium Oxide template (AAO) was fabricated by two-step anodization. The structure of the template was observed with Atomic Force Microscopy (AFM), and Scanning Electron Microscopy (SEM). Different samples, synthesized in the same anodization conditions, were treated in different pore-widening time. By raising the pore-widening time the pore diameters were increased, until they began to break in special spots. By breaking the cell's walls of the AAO template, the AAO structure was converted to alumina nanowires. Abstract: Anodic Aluminium Oxide (AAO) templates were prepared via two-step anodization by using high purity aluminium films. After second anodization, AAO templates were treated under pore-widening process, by being immersed in 5 wt% phosphoric acid. In this study, effect of pore-widening time on structure and pore diameters of AAO templates were investigated and controlling the pore-widening time, alumina nanowires were fabricated. Different techniques, such as Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM), and Energy Dispersive Spectrum (EDS) were employed to study the structure of AAO templates and alumina nanowires.